ESRA19-0521 Quadratus lumborum block (QLB) for postoperative analgesia after caesarean section: a randomised controlled trial. (30th August 2019) - Irwin, R; Stanescu, S; Buzaianu, C; Rademan, M; Gormley, C; Roddy, J; Tan, T
Abstract : Background and aims: Postoperative pain relief management remains challenging post Caesarean section. the QLB has been shown to provide satisfactory analgesia post Caesarean section under neuraxial anaesthesia. However, its utility has not been demonstrated in patients who have received spinal morphine. the aim of this study is to assess the efficacy of the QLB as part of a multi modal analgesic regimen including spinal morphine post Caesarean section. Methods: We performed a prospective, double-blind, placebo-controlled trial of 90 patients undergoing elective Caesarean section under spinal anaesthesia. Parturients were randomly allocated to receive a bilateral QLB or a sham block at the end of their surgery. the primary outcome was the difference in morphine PCA consumption over 24 hours after Caesarean section. Results: There was no significant difference in morphine PCA consumption at 24 hours between the QLB group and control group (p = 0.986). There was a statistically significant reduction in VAS (Visual Analogue Scale) pain scores at 6 hours both at rest and at movement (p = 0.019, p = 0.014 respectively). There was no significant difference in VAS pain scores at any other timepoint up to 48 hours. Conclusions: The QLB did not reduce morphine consumption at 24 hours but there was a reduction in VAS at 6 hours at rest and on movement. Increasing the local anaesthetic concentration and the addition of adjuncts could improve its analgesic profile when used in conjunction with spinal morphine.